Food Culture Analysis in Bengaluru - V. , Asha; Gupta, Heena (International Journal of Psychosocial Rehabilitation, 2020)
Bangalore is a city well known for its culture and food. There are nearly ten thousand restaurants across the entire city of Bangalore. These restaurants sometimes charge exorbitantly despite poor reviews. As per the data captured from Zomato, a food ordering app, we studied the factors like location, ratings, menu diversity, etc., majorly affecting a restaurant. The price to be charged was then predicted to realize overpricing or underpricing by comparing it with the actual price. The prediction problem is very important to assess the prices and preferences among people.